INNV-25. PATIENT CENTERED MULTI-DISCIPLINARY NEURO-ONCOLOGIC CARE AS DIRECTED BY NEW PATIENT STAKEHOLDERS. (9th November 2020) - Hunt, Rachel; Robin, Adam; Scarpace, Lisa; Gay, Nestelynn; Lee, Ian; Walbert, Tobias; Snyder, James
Abstract: Multidisciplinary oncology care requires a team of experts which should include patient stakeholders. The Henry Ford Health System (HFHS) Hermelin Brain Tumor Center (BTC) patient and family advisory council (PFAC) recommended a focus group of patient stakeholders newly diagnosed with glioblastoma(GBM) to better understand this experience. Our PFAC, comprised primarily of long-term survivors and patient advocates, felt the perspective of newly diagnosed patients may not be adequately represented. We reviewed the BTC tumor board records, identified patients within six months from GBM diagnosis, and invited these patients and their advocates to participate in an in-person session held November 2019. The BTC Patient Resource Coordinator who is also a brain tumor survivor led the session. Predefined questions prompted discussion of their neuro-oncologic care experience. Patient perspectives and recommendations were disseminated to the BTC PFAC and health system leaders. Nine patients and ten caregivers participated. Key feedback included the need for improved communication in the peri-operative period (symptom presentation until pathology results consultation). Participants requested more information prior to surgery on what to expect after surgery and with a brain tumor diagnosis. The PFAC-developed BTC experience handbook was declared useful, but patients did not receive this book until 2-weeks after surgery. As a result, we ensured that patients received a copy of the handbook at the time of diagnosis. Additionally, the development of a brain tumor surgery "prehab" course is underway. Use of a focus group to obtain input from patients recently diagnosed with GBM provided valuable insight into their experience that can be used to align care pathways with patient needs. Feedback was used to improve the delivery of neuro-oncologic care and enhance patient communication. In the constantly evolving landscape of GBM diagnosis and treatment, it is important to remain attuned to our patients' perspectives on the care we deliver.